DICOMA ANOMALA SOND.: A REVIEW OF ITS BOTANY, ETHNOMEDICINE, PHYTOCHEMISTRY AND PHARMACOLOGY - Maroyi, Alfred (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Dicoma anomala is used as herbal medicine to treat and manage fever, coughs, colds, sore throats, abdominal pain, diarrhea, dysentery, constipation, intestinal worms, and sexually transmitted infections in tropical Africa. The aim of this study was to summarize the research that has been done on the ethnomedicinal uses, phytochemistry, and pharmacological properties of D. anomala in tropical Africa. The literature search for information on ethnomedicinal uses and pharmacological activities of D. anomala was undertaken using databases such as Web of Science, Scopus, Google Scholar, Science Direct, BioMed Central, PubMed, and Springer link. Other relevant literature sources included books, book chapters, websites, theses, conference papers, and other scientific publications. This study showed that D. anomala is used as herbal medicine in 57.1% of the countries in tropical Africa where it is indigenous. The species is used to treat 66 and five human and animal diseases, respectively. Several classes of secondary metabolites including acetylenic compounds, diterpene, flavonoids, phenols, phytosterols, saponins, sesquiterpenes, tannins and triterpenes have been isolated from D. anomala. Different aqueous and organic extracts of D. anomala exhibited anthelmintic, anticancer, antihyperglycemic, anti-inflammatory, antimicrobial, antioxidant, antiplasmodial, and hepatoprotective activities. The documented information on the botany, ethnomedicinal uses, phytochemistry, and pharmacological properties of D. anomala provide baseline data required for further ethnopharmacological studies on the species.